2021
DOI: 10.1016/j.jds.2020.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of lycopene gel compared with minocycline hydrochloride microspheres as an adjunct to nonsurgical periodontal treatment: A randomised clinical trial

Abstract: Background/purpose The prescription of antibiotics as an adjunct to mechanical periodontal therapy in patients with severe periodontitis is recommended; however, the side effects of antibiotics are a major concern. The aim of this study was to evaluate the efficacy of lycopene (Lyc) antioxidant gel versus minocycline hydrochloride microspheres (ARISTIN) as an adjunct to the nonsurgical treatment of periodontitis. Materials and methods Three identical periodontal pockets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The active component in unroasted green coffee beans that gives them their antibacterial qualities is called CGA. The antioxidant properties of this extract are linked to the presence of polyphenols, which are strong antioxidants that can neutralize free radicals by donating an electron or hydrogen atom [ 15 ]. The current research findings are dependable with those of Bharath et al, who, in their in vitro study, concluded that green coffee beans were effective against four periodontopathogenic bacteria at low concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The active component in unroasted green coffee beans that gives them their antibacterial qualities is called CGA. The antioxidant properties of this extract are linked to the presence of polyphenols, which are strong antioxidants that can neutralize free radicals by donating an electron or hydrogen atom [ 15 ]. The current research findings are dependable with those of Bharath et al, who, in their in vitro study, concluded that green coffee beans were effective against four periodontopathogenic bacteria at low concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were similar to a previous research to some extent, indicating patients with periodontitis showed lower level of miR-1226 in GCF than healthy controls, and a negative correlation was found between miR-1226 expression, PPD, CAL, and BOP [18]. Nonsurgical periodontal treatments, including quadrant-wise debridement, scaling and root planning, full-mouth scaling, full-mouth disinfection (FMD), FMD with adjuvant erythritol air-polishing, and drug therapies were applied in periodontitis patients, with the purpose to improve both clinical and microbiologic outcomes [38,39]. With regard to the therapeutic implications exerted by clinical significance of miR-30b-3p and miR-125b-1-3p in periodontitis, as previously reported [40], tetramethylpyrazine is a promising agent and its anti-inflammatory and anti-apoptotic effects achieved by targeting miR-302b confer a protection to periodontal ligament stem cells from injuries induced by periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…The use of local antibiotics as adjuncts to SD for treating deep periodontal pockets has been evaluated in many studies. Compared to SD alone, better clinical outcomes could be achieved when antibiotics are locally applied, as gel or microsphere, into pockets after SD [ 103 , 104 ]. However, no clinical benefit of using local antibiotics as adjuncts to SD was reported [ 105 ].…”
Section: Evidence On Using Antimicrobials/antibiotics As Adjunct To Periodontal Therapymentioning
confidence: 99%